KAJIAN FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR GEOGRAFI DI SMA - Pantouw, Hence; Tendean, Maxi; Tuerah, Paulus Robert (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2021)
This study aims to determine the contribution of the variable of student interest in learning to motivation to learn, the contribution of the variable of parents' attention to learning motivation, the contribution of the variable of student learning facilities to learning motivation, the contribution of the variable of geography learning to learning motivation, and the contribution of the four variables together to student's motivation to study. The research uses quantitative methods, the data sources come from observations, documentation, and questionnaires, then analyzed by multiple regression analysis. The results showed that the factors that influence students' learning motivation in geography are interest factors, parental attention, learning facilities, and geography learning. The interesting factor contributes to the motivation of 0.511. The parental attention factor contributed to the motivation of 0.694. The factor of learning facilities contributed to the motivation of 0.672. The geography learning factor contributed 0.514. The overall and joint contribution of the four variables to motivation is 0.752, and the rest is influenced by other factors that are not studied in the study. The dominant factor that affects learning motivation is the parent's attention factor, which is 0.694.